2016
DOI: 10.1037/cep0000099
|View full text |Cite
|
Sign up to set email alerts
|

Rôle des afférences proprioceptives dans le développement de l’imagerie motrice chez l’enfant.

Abstract: To which extent is motor imagery (MI) development, commonly observed between the ages of 5 and 9, related to the increasing ability to integrate proprioceptive afferences for the control of action? This question was addressed in a study evaluating MI performance of 108 children aged 5, 7 and 9 years old. A mental chronometry paradigm based on a walking task was used. Integration of proprioceptive information was evaluated by comparing MI performance when children held an external load (5 % of the children weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Indeed, according to developmental studies, forward models are acquired by learning during childhood through the repetition of sensorimotor experiences. The acquisition of a systematic relation between the motor commands, the environment, and the sensory feedback generated by the movement execution will progressively allow the formation of an accurate action representation or mental movement simulation (Caeyenberghs, Tsoupas, et al ., 2009; Caeyenberghs, Wilson, et al ., 2009; Crognier et al ., 2013; Guilbert, Molina, & Jouen, 2016; Molina, Tijus, & Jouen, 2008). Therefore, the general proprioceptive dysfunction identified in DD (Quercia et al ., 2020; Quercia et al ., 2005, 2007) could be one of the origins for the action representation deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, according to developmental studies, forward models are acquired by learning during childhood through the repetition of sensorimotor experiences. The acquisition of a systematic relation between the motor commands, the environment, and the sensory feedback generated by the movement execution will progressively allow the formation of an accurate action representation or mental movement simulation (Caeyenberghs, Tsoupas, et al ., 2009; Caeyenberghs, Wilson, et al ., 2009; Crognier et al ., 2013; Guilbert, Molina, & Jouen, 2016; Molina, Tijus, & Jouen, 2008). Therefore, the general proprioceptive dysfunction identified in DD (Quercia et al ., 2020; Quercia et al ., 2005, 2007) could be one of the origins for the action representation deficit.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating motor imagery sustain this proposal. Indeed, it has been demonstrated that the easiness to simulate motor action in children is clearly linked to the richness of the afferent set of information children (Guilbert, Jouen, Lehalle, & Molina, 2013;Guilbert, Molina, & Jouen, 2016) and adolescents (Choudhury, Charman, Bird, & Blakemore, 2007) can refer to although they are not enrolled in a real action. This process of simulation has been recently proposed to give account for creativity, a cognitive process based on sensorimotor prediction.…”
Section: Introductionmentioning
confidence: 99%